Empirical essays on the economics of healthcare and education - Lee, I (2020)
This thesis consists of two chapters on healthcare and one chapter on education. Scholars and policy-makers have long recognised that health and education are important components of human capital, which in turn affect individual welfare and economic growth. This thesis aim to enhance our understanding of the drivers of healthcare quality, health outcomes, and educational performance.